(untitled) (LEARNing Landscapes, 2014)
Programming to enhance teaching on college campuses often aligns with learning models that privilege formal and structured learning activities. This qualitative study explores the informal relational learning experiences of a small sample of faculty members in the Northeast United States. Participants’ stories emphasize the relational nature of informal learning interactions which have the potential to result in perspective change. The findings highlight the value of trusting, ongoing interpersonal interaction and dialogue for meaningful faculty learning.